Redox potential and uranium sorption onto sediments: kinetic and thermodynamic characteristics. Issue 5 (27th May 2020) - Liao, Rong; Shi, Zeming; Chen, Yuejiao; Wang, Xinyu
ABSTRACT: The effects of the flooding and initial E h of sediments on the sorption of uranium onto the sediments were analysed by flooding and static experiments. The changes in uranium species with E h and kinetic and thermodynamic characteristics of the uranium sorption onto the sediments were investigated. The flooding experiment indicates that the initial E h of the sediment gradually decreased with the increase in flooding time. Based on the redox potential in the flooding experiment, simulation results obtained using the geochemical simulation software PHREEQC show that the concentration of U (VI) decreased. In contrast, the concentrations of U (III), U (IV), and U (V) gradually increased. The pseudo-second-order kinetic model well fitted the experimental data, which shows that the sorption was mainly chemical sorption. The thermodynamic parameters suggest that the entropy and enthalpy under the used conditions were positive and that ΔG θ was negative. A thermodynamic analysis shows that the sorption was endothermic and spontaneous. These results are useful for the understanding of the sorption mechanism and migration of uranium onto the sediment under different initial sediment redox potentials and provide a good theoretical foundation for radioactive pollution remediation.